Solve the simultaneous equations by using Cramer's rule. 4x = y – 5 and y = 2x + 1.

Answer:
Let 4x – y = - 5  ------------------ eq. no. (1)

and – 2x + y = 1 ----------------- eq. no. (2)


D
=
4
- 1
 =
(4× 1) – (- 2×- 1)
=
4 - 2
=
2




- 2
  1



















Dx
=
-5
-1
=
(-5× 1) – (1× -1)
=
-5 + 1
=
-4




1
1



















Dy
=
4
-5
=
(4 × 1) – (-2 ×-5)
=
4 – 10
=
-6




-2
1



















By Cramer's Rule


















x =
Dx
=
-4
=
-2







D

2
































y =
Dy
=
-6
=
-3







D

2
































Ans.
x
=
-2
and
y
=  -3






No comments:

Post a Comment